The effect of extract of ginkgo biloba addition to olanzapine on therapeutic effect and antioxidant enzyme levels in patients with schizophrenia - Atmaca, M; Tezcan, E; Kuloglu, M; Ustundag, B; Kirtas, O (Wiley, 2005)
It has been suggested that the extract of gingko biloba (EGb) may enhance the efficiency of the classic antipsychotic haloperidol in patients with chronic schizophrenia, especially on positive symptoms, and reduce serum superoxide dismutase (SOD) levels. Therefore, we decided to evaluate the therapeutic effect of EGb and to examine the effect of it on the levels of antioxidant enzymes in schizophrenic patients on olanzapine treatment. We hypothesized that EGb would have the beneficial effects on schizophrenic symptoms and might cause reductions in antioxidant enzymes. The subjects were randomly assigned to the two groups: olanzapine plus EGb (group I) (n = 15) and olanzapine alone (group II) (n = 14). The patients were evaluated at baseline and at week 8 with respect to the Positive and Negative Syndrome Scale (PANSS), serum SOD, catalase (CAT), and glutathion peroxidase (GPX) levels. At baseline, no statistically significant difference regarding the mean total PANSS scores between treatment groups was found. At the evaluation of week 8, a significant difference in mean Scale for the Assessment of Postive Symptoms (SAPS) scores but not in Scale for the Assessment of Negative Symptoms scores between groups was found. Total patients had statistically significant higher serum SOD, CAT and GPX levels compared to control groups at baseline. At 8 weeks, there were significant differences in the mean decrease in SOD and CAT levels but not in GPX levels between treatment groups. The changes in SOD and CAT levels were correlated with the change in SAPS in group I, but not in the group II. The present study supported the findings of the previous study demonstrating that EGb might enhance the efficiency of antipsychotic in patients with schizophrenia, particularly on positive symptoms of the disorder.
Keywords: antioxidant enzymes; free radical; gingko biloba; olanzapine